Investigating the export-led growth hypothesis: the Australia economy. - Tan, Susie. (2008)
We are exploring the validity of the export-growth hypothesis for Australia with quarterly data over the period 1981:3 to 1999:1 by constructing a four-variable VAR model. Multivariate Cointegration techniques are also employed to model the long-run relationship of Australia’s exports and economic growth.